2005
DOI: 10.2134/agronj2005.0040
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a Multivariate Indicator of Nitrogen Imbalance (MINI) in Potato Using Reflectance and Fluorescence Spectroscopy

Abstract: trient concentration in the leaves (Beaufils, 1973). Those dual ratios represent the minimum expression for nutri-In this study, we evaluated the potential of reflectance and fluoresent interactions. Parent and Dafir (1992) developed a cence for the detection of the Compositional Nutrient Diagnosis (CND) N index (I N ). The CND reflects nutrient deficiencies as well new indicator of plant nutritional status: the CND. The as nutrient interactions, contrary to conventional methods of nutrient CND not only evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A similar trend was reported by Heisel et al (1997) for wheat (Triticum aestivum L.), but Campbell et al (2007) found that BGF decreases in corn with N at high N application rates. For most species and conditions, F(UV-B)/F(BG) ratios are higher for abaxial than adaxial leaf surfaces (Barnes et al 2000). Blue-green fluorescence has been used in conjunction with ChlF to detect plant stress and identify plant types (Chappelle and Williams 1987;Chappelle et al 1991).…”
Section: N-induced Changes and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar trend was reported by Heisel et al (1997) for wheat (Triticum aestivum L.), but Campbell et al (2007) found that BGF decreases in corn with N at high N application rates. For most species and conditions, F(UV-B)/F(BG) ratios are higher for abaxial than adaxial leaf surfaces (Barnes et al 2000). Blue-green fluorescence has been used in conjunction with ChlF to detect plant stress and identify plant types (Chappelle and Williams 1987;Chappelle et al 1991).…”
Section: N-induced Changes and Applicationsmentioning
confidence: 99%
“…Ounis et al (2001) showed that the epidermal UV absorption of vegetation can be estimated from the ChlF excitation ratio, ФF(532)/ФF(355). Bilger et al (1997) and Barnes et al (2000) reported that noninvasive estimates of epidermal transmittance of UV radiation using ChlF can detect changes in pigmentation and in leaf optical properties induced by UV-B radiation under both field and laboratory conditions. Samson et al (2000) found that Phen may be a more specific indicator of crop N status than Chl because the latter is sensitive to sulfur deficiency.…”
Section: N-induced Changes and Applicationsmentioning
confidence: 99%
“…Fluorescence measurements are often combined with Vis-NIR. Using multivariate data analysis, this enabled distinction between N sufficient and N deficient potato plants in a greenhouse experiment, even when combined with K and Mg deficiencies ( Bélanger et al, 2005 ). A newly developed, hand-held instrument, Dualex ® , determines crop N status by measuring the NBI, which is the chlorophyll concentration divided by the concentration of flavonoids.…”
Section: Methods Of Plant Mineral Analysismentioning
confidence: 99%
“…14.5 Development of New Methods of Crop Sensing Bélanger et al (2005) proposed the use of a multivariate indicator to detect nutrient deficiencies in crops and proposed for potato (Solanum tuberosum L.) that a multivariate indicator of nitrogen imbalance (MINI) based on reflectance and fluorescence indices would be useful. They used reflectance indices based on combinations of wavebands and simple ratios and found that MINI could correctly detect 70 % of the nitrogen-deficient plants and 90 % of the nitrogen-sufficient plants, and this method would be more rapid than the current method of tissue testing.…”
Section: Application To Other Cropsmentioning
confidence: 99%